Historical aspects of standard negation in Semitic - Sjörs, Ambjörn (Studies in Semitic languages and linguistics, 2018)
Front Matter -- Copyright page -- Preface -- List of Tables and Diagrams -- Abbreviations, Terminology, and Symbols -- Introduction -- Preliminaries -- On the Grammar of Negation -- Presentation and Analysis of the Material -- Old Assyrian and East Semitic -- Ugaritic -- Standard Biblical Hebrew -- Phoenician -- Aramaic, Deir Alla, and Sam’alian -- Quran Arabic -- Minaic, Sabaic, and Ancient South Arabian -- Jibbali and Modern South Arabian -- Tigre and Tigrinya -- Amharic and Harari -- Gafat, Kistane, and Peripheral Western Gurage -- Concluding Discussion -- Innovative Expressions of Negation -- Other Negators and Negative Asymmetries -- Reconstruction.